Better for us to be food sufficient - Abd Razak, Dzulkifli (2008)
THE melamine food contamination issue, though not dominating news headlines any more, is far from over. Chinese baby formula tainted with the toxic substance is really the tip of the iceberg. Of late, we have read of other food categories that were also contaminated, including vegetables, fruits and other types of candies or snacks, affecting no less than 40 countries. Though there have been many test results claiming that certain food brands are safe for consumption, there are still many others that could be on the "suspect" list.